Water-Soluble Iridium(III) Complexes Containing Tetraethylene-Glycol-Derivatized Bipyridine Ligands for Electrogenerated Chemiluminescence Detection - Newman, Ben; Chen, Lifen; Henderson, Luke C.; Doeven, Egan H.; Francis, Paul S.; Hayne, David J. (Frontiers in Chemistry, 2020)
Four cationic heteroleptic iridium(III) complexes containing a 2,2′-bipyridine (bpy) ligand with one or two tetraethylene glycol (TEG) groups attached in the 4 or 4,4′ positions, were synthesized to create new water-soluble electrogenerated chemiluminescence (ECL) luminophores bearing a convenient point of attachment for the development of ECL-labels. The novel TEG-derivatized bipyridines were incorporated into [Ir(C^N)2(R-bpy-R′)]Cl complexes, where C^N = 2-phenylpyridine anion (ppy) or 2-phenylbenzo[d]thiazole anion (bt), through reaction with commercially available ([Ir(C^N)2(u-Cl)]2 dimers. The novel [Ir(C^N)2(Me-bpy-TEG)]Cl and [Ir(C^N)2(TEG-bpy-TEG)]Cl complexes in aqueous solution largely retained the redox potentials and emission spectra of the parent [Ir(C^N)2(Me-bpy-Me)]PF6 (where Me-bpy-Me = 4,4′methyl-2,2′-bipyridine) luminophores in acetonitrile, and exhibited ECL intensities similar to those of [Ru(bpy)3]2+ and the analogous [Ir(C^N)2(pt-TEG]Cl complexes (where pt-TEG = 1-(TEG)-4-(2-pyridyl)-1,2,3-triazole). These complexes can be readily adapted for bioconjugation and considering the spectral distributions of [Ir(ppy)2(Me-bpy-TEG)]+ and [Ir(ppy)2(pt-TEG)]+, show a viable strategy to create ECL-labels with different emission colors from the same commercial [Ir(ppy)2(u-Cl)]2 precursor.